2014
DOI: 10.1016/j.jval.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Choice Experiment to Estimate Breast Cancer Patients’ Preferences and Willingness to Pay for Prophylactic Granulocyte Colony-Stimulating Factors

Abstract: Participants highly valued specific features of prophylactic G-CSF treatment including maintaining their chemotherapy schedule, lowering their risk of infection, and reducing the number of injections. Physicians should consider patient preferences to inform the best treatment choices for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 39 publications
0
24
1
Order By: Relevance
“…In other words, patients could accept higher risk for anemia to trade for PFS. Our results were inconsistent with the results from an only previous DCE study on breast cancer patients’ preference for prophylactic granulocyte colony-stimulating factors (Johnson et al 2014 ). Even though they might not be a good comparison due to various differences, e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…In other words, patients could accept higher risk for anemia to trade for PFS. Our results were inconsistent with the results from an only previous DCE study on breast cancer patients’ preference for prophylactic granulocyte colony-stimulating factors (Johnson et al 2014 ). Even though they might not be a good comparison due to various differences, e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Johnson and colleagues conducted a discrete choice experiment to explore willingness to pay for prophylactic granulocyte colony-stimulating factor to decrease the risk of febrile neutropenia. 27 In this study, patients were willing to pay more than $1,000 to reduce the risk of disrupting their chemotherapy schedule, and more than $800 to reduce the risk of infection. 27 Among patients with non-Hodgkin lymphoma, a similar experiment found that for each $10 increase in out-of-pocket costs, the adjusted odds ratio for accepting outpatient care for febrile neutropenia was 0.84.…”
Section: The Cost Of Cancer Carementioning
confidence: 99%
“…27 In this study, patients were willing to pay more than $1,000 to reduce the risk of disrupting their chemotherapy schedule, and more than $800 to reduce the risk of infection. 27 Among patients with non-Hodgkin lymphoma, a similar experiment found that for each $10 increase in out-of-pocket costs, the adjusted odds ratio for accepting outpatient care for febrile neutropenia was 0.84. 28 It is interesting to note that the adjusted odds ratio for accepting outpatient care was even lower (0.53) for each 5% increase in probability of return to the hospital, suggesting that risk of hospitalization may be a greater deterrent than small increases in out-of-pocket costs.…”
Section: The Cost Of Cancer Carementioning
confidence: 99%
“…A DCE is appropriate for this type of research because preference weights derived from a DCE are estimated on a common scale and can be used to calculate ratios describing the trade-offs respondents are willing to make among the attributes. Examples of these trade-offs include estimates of money equivalence (willingness to pay) [30,31], risk equivalence (maximum acceptable risk) [18,32], or time equivalence [33,34] for various changes in attributes or attribute levels. Although the underlying premise and the mechanics of using a DCE are similar in market research and outcomes research, the objectives of using a DCE typically differ between these disciplines.…”
Section: Introductionmentioning
confidence: 99%